A CONFIRMATORY FACTOR ANALYSIS OF THE INTERGENERATIONAL TENSION SCALE. (11th November 2018) - Intrieri, R; McCall, G
Abstract: North and Fiske (2013) have developed a novel ageism scale that specifically focuses on prescriptive beliefs about intergenerational tension. The Intergenerational Tension Scale is composed of three subscales: Succession, Identity, and Consumption (SIC). Succession refers to active progression into enviable positions of power and influence, that is older adults would step away from employment positions or positions of power (through retirement) to allow younger adults to rise in the workforce and political influence. Identity is described as age-appropriate, symbolic maintenance of who the individual is as a person and means that older adults should limit their participation in activities usually set aside for younger adults (e. g., participation in the club or party scene). Consumption is associated with the exhaustion of presently pooled resources and characterizes draining or not draining resources so that there is nothing left for the succeeding generations. The purpose of this study is to validate the three-factor model of North and Fiske. (2013). The sample included 337 women and 168 men (n = 505). Mean ages for men and women were 19.74 (SD = 1.74) and 19.58 (SD = 1.45), respectively (Mtotal = 19.63, SDtotal = 1.55). Results of a confirmatory factor analysis showed the three factor model exhibited a reasonable fit to the data C2 (162, N = 505) = 436.72; p<.0001, CFI =.906; TLI =.890; RMSEA =. 058, SRMS = .05. Results and further adjustments to the model will be discussed.